Diaconia Beyond Borders: Welfare State, Church, and Migrants with Limited Welfare Rights (Tidsskrift for Praktisk Teologi, 2023)
The presence of migrants in precarious life situations with limited welfare rights challenges the Nordic national churches to reconsider their role vis-à-vis the welfare state. The aim of this article is to discuss what such a reorientation should imply. Through an engagement with the works of William T. Cavanaugh, Gustaf Wingren, and Gyrid Gunnes, I argue for a church of diaconia that takes the situation of migrants with limited welfare rights into account by being a space of recapitulation and justice, while at the same time keeping the welfare state accountable to its responsibility of protecting vulnerable lives.